The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.26555/humanitas.v13i1.3846
|View full text |Cite
|
Sign up to set email alerts
|

Benarkah Self Esteem Mempengaruhi Prestasi Akademik?

Abstract: Self-esteem determines a person's overall mental development, it can even affect human behavior. The debate arose when researchers try to explain, whether student achievement is influenced by self-esteem? The author conducted a meta-analysis studies in attempt to clarify the relationship between the variables of self-esteem with academic achievement variable. This research analyzed over sixteen research journals, in which there are 29 studies that examine a relationship between self-esteem and academic achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
2
10
0
5
Order By: Relevance
“…Finally, for the third and the main finding, the study results also support the findings from previous studies (e.g., Mirzaei-Alavijeh et al, 2018;Wibowo, 2016;Rosli et al, 2011;Aryana, 2010;Sandra, 2009;Habibollah et al, 2008;Sadaat et al, 2012) who all cited a positive correlation between self-esteem and academic performance. However, the findings differ from Van Laar's (2000) study who found that there is little to no relationship between self-esteem and academic success in African American students.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, for the third and the main finding, the study results also support the findings from previous studies (e.g., Mirzaei-Alavijeh et al, 2018;Wibowo, 2016;Rosli et al, 2011;Aryana, 2010;Sandra, 2009;Habibollah et al, 2008;Sadaat et al, 2012) who all cited a positive correlation between self-esteem and academic performance. However, the findings differ from Van Laar's (2000) study who found that there is little to no relationship between self-esteem and academic success in African American students.…”
Section: Discussionsupporting
confidence: 89%
“…While increasing the learners' self-esteem can help to improve their academic performance (Rubie et al, 2004), a poor academic attainment does not necessarily display a low general self-confidence (Pullmann & Allik, 2008). At the same time, other studies have found a significant but weak correlation between the two variables (Wibowo, 2016) and self-esteem has a weak positive effect on academic achievement (Marsh & O'Mara, 2008). Although much attention has been given to the relationships between self-esteem and academic performance (Jordan, et al, 2015;Doodman, et al, 2017), similar studies are very limited in Malaysia especially among undergraduates of private universities and the lack of literature necessitates an empirical study.…”
Section: Self-esteem and Academic Achievement: The Relationship And Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, they will be more confident and consider their self-valuable, important and must be respected, able to influence others with creative ideas, become more optimistic, love new and challenging tasks, expect for success. Wibowo (2016) through his research also proves the influence of self-esteem toward students' academic achievement. Students who have high self-esteem have high academic achievement.…”
Section: The Definition Of Self-esteemmentioning
confidence: 81%
“…Tambunan juga menyatakan bahwa ada hubungan positif antara kemampuan spasial dengan prestasi belajar matematika baik kemampuan spasial total maupun kemampuan spasial euclidis [9]. Hal ini sejalan dengan hasil penelitian Wibowo yang menunjukkan bahwa terdapat korelasi yang signifikan antara self esteem dengan prestasi akademik [10]. Dalam penelitiannya dijelaskan bahwa hubungan antara seft esteem dengan prestasi akademik bersifat dua arah, bisa jadi self esteem mempengaruhi prestasi akademik, atau sebaliknya prestasi akademik mempengaruhi self esteem.…”
Section: Pendahuluanunclassified